Design and biological evaluation of 3-substituted quinazoline-2,4(1H,3H)-dione derivatives as dual c-Met/VEGFR-2-TK inhibitors - Abdelfattah Hassan; Fawzy A. F. Mubarak; Ihsan A. Shehadi; Ahmed M. Mosallam; Hussain Temairk; Mohamed Badr; Aboubakr H. Abdelmonsef (Taylor & Francis Group, 2023)
The dual c-Met/vascular endothelial growth factor receptor 2 (VEGFR-2) TK inhibition is a good strategy to overcome therapeutic resistance to small molecules VEGFR-2 inhibitors. In this study, we designed 3-substituted quinazoline-2,4(1H,3H)-dione derivatives as dual c-Met/VEGFR-2 TK inhibitors. We introduced new synthetic methods for reported derivatives of 3-substituted quinazoline-2,4(1H,3H)-dione 2a-g, in addition to the preparation of some new derivatives namely, 3 and 4a-j. Three compounds namely, 2c, 4b, and 4e showed substantial amount of inhibition for both c-Met and VEGFR-2 TK (IC50 range 0.052-0.084 µM). Both compounds 4b, 4e showed HB with highly conserved residue Asp1222 in the HB region of c-Met TK. For VEGFR-2 TK, compound 4b showed HB with a highly conserved residue Asp1046 in the HB region. Compound 4e showed HB with Glu885 and Asp1046. Moreover, in silico prediction of pharmacokinetic and physicochemical parameters of target compounds was carried out using SwissADME website. The quinazoline-2,4(1H,3H)-dione derivatives are promising antiproliferative candidates that require further optimisation.